Functional interfaces between TICAM-2/TRAM and TICAM-1/TRIF in TLR4 signaling. (16th June 2017) - Funami, Kenji; Matsumoto, Misako; Oshiumi, Hiroyuki; Inagaki, Fuyuhiko; Seya, Tsukasa
Abstract : Toll-like receptor 4 (TLR4) recognizes lipopolysaccharide (LPS), produces pro-inflammatory cytokines and type I interferons, and associates with a trigger of endotoxin shock. TLR4 is interacted with a TIR domain-containing adaptor molecule-2 (TICAM-2)/TRAM [TRIF (TIR domain-containing adaptor-inducing interferon-β)-related adaptor molecule] via its Toll–interleukin-1 receptor homology (TIR) domain. TICAM-2 acts as a scaffold protein and activates TIR domain-containing adaptor molecule-1 (TICAM-1)/TRIF. According to the structural analysis by NMR, TICAM-2 interacts with TICAM-1 by the acidic amino acids motif, E87/D88/D89. The TIR domain of TICAM-2 couples with the dimer of TIR domain of TLR4 beneath the membrane, and TICAM-2 itself also forms dimer and constitutes a binding site with TICAM-1. Endosomal localization of TICAM-2 is essential for TLR4-mediated type I interferon-inducing signal from the endosome. N-terminal myristoylation allows TICAM-2 to anchor to the endosomal membrane. Additionally, we have identified two acidic amino acids, D91/E92, as a functional motif that cooperatively determines endosomal localization of TICAM-2. This structural information of TICAM-2 suggests that the specific structure is indispensable for the endosomal localization and type I interferon production of TICAM-2. Taken together with the knowledge on cytoplasmic sensors for LPS, TICAM-2/TICAM-1 may conform to a signal network on TLR4 to facilitate induction of cytokine disorders.